METHYLSENSITIVE COMET ASSAY: ANALYSIS OF DNA METHYLATION LEVEL IN GLIOBLASTOMA T98G CELL LINE - СВИРИДОВА, Катерина; АФАНАСЬЄВА, Катерина (Київський національний університет імені Тараса Шевченка, 2023)
Methylsensitive comet electrophoresis is based on the assessment of the level of DNA migration from individual lysed cells after treatment with methylsensitive restriction enzymes. Using model human lymphocytes, the optimal combination of restriction intensity and electrophoresis time was selected and a new approach for evaluating the relative level of DNA methylation was proposed. It was established that in the cells of the T98G culture, which are actively proliferating, the level of methylation is higher than in cells arrested at the G1 phase of the cell cycle. At the same time, the level of DNA methylation in G1 cells of the T98G line is significantly lower compared to lymphocytes.

Метилчутливий кометний електрофорез базується на оцінці рівня міграції ДНК із індивідуальних лізованих клітин після обробки метилчутливими рестриктазами. Використовуючи модельні лімфоцити людини, було підібрано оптимальну комбінацію інтенсивності рестрикції і часу електрофорезу та запропоновано новий підхід для оцінювання відносного рівня метилування ДНК. Було встановлено, що в культурі клітин лінії T98G, які активно діляться, рівень метилування є вищим, ніж у клітин, що перебувають на стадії G1 клітинного циклу. При цьому рівень метилування ДНК у G1-клітинах лінії T98G достовірно нижчий порівняно з лімфоцитами.
МЕТИЛЧУТЛИВИЙ КОМЕТНИЙ ЕЛЕКТРОФОРЕЗ: АНАЛІЗ РІВНЯ МЕТИЛУВАННЯ ДНК У КЛІТИНАХ ГЛІОБЛАСТОМИ ЛІНІЇ Т98G
Keywords: Злоякісно-трансформовані клітини гліобластоми; лімфоцити периферичної крові людини; метилування ДНК; кометний електрофорез; Glioblastoma cancer cells; human peripheral blood lymphocytes; DNA methylation; comet assay; DNA methylation